1989
DOI: 10.1139/z89-222
|View full text |Cite
|
Sign up to set email alerts
|

Responses of several fish species to pH gradients

Abstract: The responses of 11 fish species to a continuous pH gradient (usually pH 4–10) were observed to obtain information on avoidance–preference behavior. Under uniform pH conditions, all species were found most frequently near the ends of the apparatus, particularly near the inflow. Imposition of a pH gradient altered the distribution for most species, with the region of lowest pH usually being avoided. Estimated low pH avoidance thresholds were 4.1 for yellow perch, 4.5 for white sucker, 4.7 for brook charr, 5.1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 12 publications
7
30
1
Order By: Relevance
“…1e), and consequently that of zooplankton when phytoplankton biomass is not so high to cause growth inhibition (Liady et al 2015 and references there in). Indeed, the extent of pH preferences for fish is usually 5-7 to 7-9 (Peterson et al 1989). Our findings were like those obtained by Bokossa et al (2014a).…”
Section: Effect Of Rabbit Manure On Nutrient Dynamics and Water Qualitysupporting
confidence: 89%
“…1e), and consequently that of zooplankton when phytoplankton biomass is not so high to cause growth inhibition (Liady et al 2015 and references there in). Indeed, the extent of pH preferences for fish is usually 5-7 to 7-9 (Peterson et al 1989). Our findings were like those obtained by Bokossa et al (2014a).…”
Section: Effect Of Rabbit Manure On Nutrient Dynamics and Water Qualitysupporting
confidence: 89%
“…Fish in the wild may respond to several environmental factors (Gunn & Noakes, 1986), and laboratory experiments may separate and clarify these responses (Peterson et al, 1989). Previous study demonstrated that uninfected silver catfish juveniles at water hardness of 24 mg CaCO 3 L -1 preferred the 7.0-7.6 pH range (Riffel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several others species also showed preference to a specific pH (Peterson et al, 1989). Japanese fat minnows (Phoxinus lagowski) presented avoidance behavior and their swimming region shifted from pH 6.0 to 7.0 immediately after decreasing pH and during the exposure to acidic water their swimming activity clearly decreased (Nakamura, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral research into the role of chemoreception in fish has expanded to include potential environmental stressors, such as temperature (Richardson et al 1994), acidification (Jones et al 1985a(Jones et al , 1985bPeterson et al 1988), turbidity (Cyrus and Blaber 1987;Boubée et al 1997), and aquatic pollutants (Brown et al 1981). This work has built on the knowledge and expertise gained from behavioral research on individual recognition (Olsén 1989;Olsén and Winberg 1996), schooling (Keenleyside 1955), homing in salmonids (Cooper and Hirsch 1981;Erkinaro et al 1999), reproductive behavior (Liley and Stacey 1983;Olsén et al 1998), and alarm substance (Pfeiffer 1981).…”
mentioning
confidence: 99%